2011
DOI: 10.1590/s0100-69912011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Estudo morfométrico da divisão arterial do baço comparado ao estudo radiológico

Abstract: OBJETIVO: Estudar a distribuição dos ramos da artéria esplênica dirigidos ao baço aplicado ao estudo radiológico da sua distribuição intraparenquimatosa, visando à utilização destes conhecimentos na esplenectomia parcial. MÉTODOS: no estudo macroscópico, foram utilizados 60 baços humanos dos quais as artérias esplênicas foram dissecadas desde sua origem para visualizar a divisão terminal e os ramos dirigidos ao baço. Realizaram-se as medidas da distância entre a face visceral do baço e a divisão terminal da ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…The trifurcated presentation was present in 4.53%. The findings are similar to those observed in a Brazilian study with 60 arteriographies, in which the bifurcated type appeared in 93.3%, and the trifurcated, in 6.7% 20 . Regarding terminal splenic ramifications, the most frequently found were those of three (34.90%) and four arteries (34.10%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The trifurcated presentation was present in 4.53%. The findings are similar to those observed in a Brazilian study with 60 arteriographies, in which the bifurcated type appeared in 93.3%, and the trifurcated, in 6.7% 20 . Regarding terminal splenic ramifications, the most frequently found were those of three (34.90%) and four arteries (34.10%).…”
Section: Discussionsupporting
confidence: 91%
“…Knowledge of the intraparenchymal division of the splenic artery is essential in partial splenectomy. Therefore, understanding the vascular network presentation facilitates its rapid identification and characterizes an important parameter for surgical guidance 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achado também encontrado com pouca frequência nos estudos de Melo (2011), em cervídeos, Takci (2009), em bovinos, e Schimming e Abreu (2001), em tatus. A ramificação extraparenquimatosa com ramos colaterais, secundários ou terciários da artéria esplênica, dirigidos às extremidades do baço, recebem a denominação de artérias polares em humanos, como observado na extremidade dorsal no baço de cutias, e são relativamente importantes na orientação dos cirurgiões no momento de realizar a desvascularização de determinada área do órgão (SILVA et al, 2011).…”
Section: Resultsunclassified
“…Furthermore, the length of a splenic polar artery in reference to the distance from its point of origin to the splenic hilum is an additional clinically relevant feature. An investigation by Silva et al examined 11 splenic polar arteries and found the average distance between the arterial point of origin and the splenic hilum was 4.85 cm [ 17 ]. This greatly contrasts with the distance of 8.0 cm described in this case presentation.…”
Section: Discussionmentioning
confidence: 99%